2012
DOI: 10.1007/s00394-012-0439-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining acute and chronic effects of short- and long-chain fatty acids on peptide YY (PYY) gene expression, cellular storage and secretion in STC-1 cells

Abstract: Our studies demonstrate the potential usefulness of STC-1 cells as an in vitro model for investigating nutrient-stimulated PYY secretion in an acute setting. Furthermore, our discovery that CLA directly stimulates L-cells to secrete PYY indicates another possible mechanism contributing to the observed effects of dietary CLA on weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 45 publications
2
32
0
1
Order By: Relevance
“…In accordance with a previous study in GLUTag and STC-1 cells (Drucker et al 1994), insulin was not detected in any of the cell lines. Our results also confirm data from other studies regarding the presence of GLP-2 in GLUTag and STC-1 cells, and the ability of GLUTag and in particular STC-1 cells, to produce and secrete CCK (Cordier-Bussat et al 1997, Hand et al 2010, Hand et al 2013, Nemoz-Gaillard et al 1998, Sidhu et al 2000.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance with a previous study in GLUTag and STC-1 cells (Drucker et al 1994), insulin was not detected in any of the cell lines. Our results also confirm data from other studies regarding the presence of GLP-2 in GLUTag and STC-1 cells, and the ability of GLUTag and in particular STC-1 cells, to produce and secrete CCK (Cordier-Bussat et al 1997, Hand et al 2010, Hand et al 2013, Nemoz-Gaillard et al 1998, Sidhu et al 2000.…”
Section: Discussionsupporting
confidence: 82%
“…A few studies have reported measurable PYY storage in and secretion from STC-1 cells (Geraedts et al 2009, Hand et al 2013, but the study by Geraedts et al (2009) reports measured concentrations that either are below or at the lower level of detection as reported by the assay manufacturers. However, given that the other peptides measured in our study were present at very high levels, combined with the lower limit of detection sensitivity (< 1 pM) of the applied assays for PYY measurement in this study, we consider it unlikely that our results are erroneous.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to CCK, STC-1 cells express and secrete a wide range of gut hormones known for their roles in metabolism, feeding and satiety, including glucose dependent insulinotropic polypeptide (GIP), peptide YY (PYY), pancreatic polypeptide, neurotensin and the proglucagon derived peptides [glucogon-like peptide-1 (GLP-1), glucogon-like peptide-2 (GLP-2) and oxyntomodulin] (Rindi et al 1990 ;Hand et al 2013 ). STC-1 cells secrete these hormones in response to a range of physiological stimuli, although levels may differ to native enteroendocrine cells (Reimann et al 2008 ).…”
Section: Features and Mechanismsmentioning
confidence: 99%
“…Interestingly, these substances do not appear to be GLP-1 stimulants in primary cultures of murine intestinal epithelium (Reimann et al 2008 ). Although PYY secretion has been less widely investigated, STC-1 cells reliably produce and secrete PYY in response to a variety of fatty acids including valeric acid, linoleic acid and conjugated linoleic acid 9,11 (Hand et al 2013 ). GIP expression and production by STC-1 cells is poor.…”
Section: Features and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation